2009
DOI: 10.1158/0008-5472.can-08-2627
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Mitogen-Activated Protein Kinase Kinase 1/2 Inhibitor with a Unique Mechanism of Action for Cancer Therapy

Abstract: The mitogen-activated protein kinase (MAPK) signal transduction pathway plays a central role in regulating tumor cell growth, survival, differentiation, and angiogenesis. The key components of the Ras/Raf/MEK/ERK signal module are frequently altered in human cancers. Targeting this pathway represents a promising anticancer strategy. Small molecule inhibitors targeting MEK1/2 have shown promise in the clinic; however, ultimate clinical proof-of-concept remains elusive. Here, we report a potent and highly select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 21 publications
4
38
1
1
Order By: Relevance
“…Besides, SIP has been found to interact with ERK1/2 and downregulate ERK activity (Kilanczyk et al, 2009). Furthermore, suppression of the ERK-involved pathway sensitizes cancer cells to apoptosis (Tran et al, 2001;Wu et al, 2004) and a series of inhibitors targeting ERK pathway have been identified as potential anti-cancer drugs (Daouti et al, 2009). It has also been shown that SIP serves as a molecular bridge between Siah-1 and Skp1 proteins, and forms a ubiquitin ligase complex together with Ebi and in turn promotes b-catenin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, SIP has been found to interact with ERK1/2 and downregulate ERK activity (Kilanczyk et al, 2009). Furthermore, suppression of the ERK-involved pathway sensitizes cancer cells to apoptosis (Tran et al, 2001;Wu et al, 2004) and a series of inhibitors targeting ERK pathway have been identified as potential anti-cancer drugs (Daouti et al, 2009). It has also been shown that SIP serves as a molecular bridge between Siah-1 and Skp1 proteins, and forms a ubiquitin ligase complex together with Ebi and in turn promotes b-catenin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Both agents have shown some clinical benefits including partial response and stable disease, but have also revealed potential safety issues that were not known to be mechanism or chemo-type related (15,16). We have identified a new class of MEK inhibitors with a novel structure and a unique mechanism of action that may offer differential clinical benefit in cancer patients (17). Many challenges remain in the development of MEK inhibitors: (a) the selection of the most responsive patient population; (b) the use of biochemical markers for early proof of mechanism of action and to define an optimal dose regimen for target inhibition; (c) the use of surrogate markers to predict early response; and (d) the selection of optimal combination partners and regimens for rational combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported a new class of MEK inhibitors with novel chemical structure and mechanism of action (17). RO5068760 belongs to this class and exhibits a unique mode of MAPK signal blockade.…”
Section: Molecularmentioning
confidence: 99%
See 2 more Smart Citations